2018
DOI: 10.1186/s12943-018-0880-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosome–transmitted long non-coding RNA PTENP1 suppresses bladder cancer progression

Abstract: BackgroundExtracellular communication within the tumor microenvironment plays a critical role in tumor progression. Although exosomes can package into long non-coding RNAs (lncRNAs) to mediate extracellular communication, the role of exosomal lncRNA PTENP1 in bladder cancer (BC) remains unclear.MethodWe detected PTENP1 expression between patients with BC and healthy controls; the expression occurred in tissues and exosomes from plasma. We assessed the diagnostic accuracy by the receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(172 citation statements)
references
References 49 publications
2
169
1
Order By: Relevance
“…Cancer-related reports involve a large quantity of data on the effects of EVs circRNAs. 29 With efforts made in this study, it was QRT-PCR results showed that circ-0000190 was primarily distributed in the cytoplasmic fraction of osteosarcoma cells. 28 For instance, EVs from normal cells transferred PTENP1 to bladder cells, which suppresses bladder cancer progression.…”
Section: Discussionmentioning
confidence: 78%
“…Cancer-related reports involve a large quantity of data on the effects of EVs circRNAs. 29 With efforts made in this study, it was QRT-PCR results showed that circ-0000190 was primarily distributed in the cytoplasmic fraction of osteosarcoma cells. 28 For instance, EVs from normal cells transferred PTENP1 to bladder cells, which suppresses bladder cancer progression.…”
Section: Discussionmentioning
confidence: 78%
“…Exosomes secreted by human colon cancer cells can transmit miR-210 to neighboring metastatic cells to influence their adhesion (Bigagli, Luceri, Guasti, & Cinci, 2016). Similarly, exosome-transmitted long ncRNA PTENP1 participates in normal-cell-to-bladder-cell communication during the carcinogenesis of bladder cancer (Zheng et al, 2018). Our study revealed that exosomes act as intercellular communicators to transmit miR-221 to normal recipient cells to increase cell viability, but the mechanism needs further investigation.…”
Section: Discussionmentioning
confidence: 71%
“…Cell cycle was analyzed as described previously (Zheng et al ). After treatment with PNP, T24 cells were harvested and suspended in 70% cold ethanol and then incubated overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle was analyzed as described previously (Zheng et al 2018). After treatment with PNP, T24 cells were harvested and suspended in 70% cold ethanol and then incubated overnight at 4 C. After centrifugation, the cells were washed with cold PBS, then suspended in 500 μL PBS, and incubated with 50 μL RNase A (20 μg/mL terminal concentration) for 30 min.…”
Section: Cell Cycle Analysismentioning
confidence: 99%